Dampak Kredit Terhadap Ekonomi Rumah tangga Petani Kopi di Kabupaten Pati - Stevana Astra Jaya; Harianto Harianto; M. Parulian Hutagaol (Politeknik Negeri Lampung, 2017)
Plantation sub-sector is one of the agricultural sector mainstays of the foreign exchange and source of household farmers’ income. Plantation development is intended to make it more efficient, productive and competitive in order to increase the income of coffee farmers and their families. The main problem is the poverty of coffee farmers. Coffee plantations owned by coffee farmers in Pati are still dominated by small-scale enterprises, technologically simple, and low income. With low capital conditions, to help increase production and income of coffee farmers, loans are channeled through savings and loan program by Sido Makmur farmer group as an economic empowerment program for coffee farmer households. The aim of this research was to analyze the impact of the loans from Sido Makmur farmer groups toward household economy of coffee farmers. The study was conducted in coffee plantations in Klakahkasihan Village, Gembong, Pati. Cross - section data from Sido Makmur farmer group in Klakahkasihan village were collected directly from 52 respondents; they were 32 farmers who took the loans and 20 farmers who did not. The method used to analyze the data is simultaneous equation model. The results showed that loan has a negative impact on coffee production. It means that less amount of loan taken will improve coffee production. However, the loan has a positive impact on the non - food household consumption, meaning that greater loan taken will increase the household consumption of non – food goods. It can be concluded that this loan failed to help increase the production of coffee, because coffee farmers used it for the household consumption of non – food goods. Keywords: loan, household economy, coffee plantanation, Sido Makmur farmer group, Pati.